Methodological approach to managing the development of a main mining design: A case study of the X-Ray plant at the Gacko open-pit mine - Jovanović Nikola; Stefanović Jelena; Živanović Miloš; Pavlović Zlatko; Miljković Nikola; Avramović Zoran (Mining and Metallurgy Engineering Bor, 2025)
The paper presents an approach to managing the development of the main mining project for an X-Ray sensor-based coal sorting plant under complex technical and organizational conditions at the Gacko open-pit mine. The project team was virtual in nature, consisting of members from multiple countries and disciplines. Through the application of modern project management tools (OBS, WBS, MS Project), the efficiency of planning, control, and risk management was analyzed. The results highlight the importance of a multidisciplinary and digitally integrated approach in the implementation of complex mining projects.